2002
DOI: 10.1172/jci14459
|View full text |Cite
|
Sign up to set email alerts
|

The prostaglandin receptor EP4 suppresses colitis, mucosal damage and CD4 cell activation in the gut

Abstract: We used mice deficient in each of the eight types and subtypes of prostanoid receptors and examined the roles of prostanoids in dextran sodium sulfate–induced (DSS-induced) colitis. Among the prostanoid receptor–deficient mice, only EP4-deficient mice and not mice deficient in either DP, EP1, EP2, EP3, FP, IP, or TP developed severe colitis with 3% DSS treatment, which induced only marginal colitis in wild-type mice. This phenotype was mimicked in wild-type mice by administration of an EP4-selective antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 45 publications
5
130
0
Order By: Relevance
“…Recent reports have shown that exogenously applied PGE 2 attenuated DSS-induced colitis and promoted epithelial proliferation [25,34,35] suggesting that endogenous PGE 2 is the mediator of mucosal protection. PGE 2 exerts anti-inflammatory effects including suppression of neutrophil function or prevention of mast cell degranulation [36] as well as suppressor T-cell induction and inhibition of the production and release of proinflammatory cytokines such as TNF-a, IL-1b and IL-12 by macrophages and neutrophils [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have shown that exogenously applied PGE 2 attenuated DSS-induced colitis and promoted epithelial proliferation [25,34,35] suggesting that endogenous PGE 2 is the mediator of mucosal protection. PGE 2 exerts anti-inflammatory effects including suppression of neutrophil function or prevention of mast cell degranulation [36] as well as suppressor T-cell induction and inhibition of the production and release of proinflammatory cytokines such as TNF-a, IL-1b and IL-12 by macrophages and neutrophils [35].…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 exerts anti-inflammatory effects including suppression of neutrophil function or prevention of mast cell degranulation [36] as well as suppressor T-cell induction and inhibition of the production and release of proinflammatory cytokines such as TNF-a, IL-1b and IL-12 by macrophages and neutrophils [35]. Also PGE 2 plays a major role in the generation of the epithelial crypts after DSS-induced intestinal damage in mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many groups have examined the recovery phase after a single administration of DSS. 93,[132][133][134][135][136] Both acquired and innate immune responses have been implicated in the recovery phase, 93,132 and the epithelial cell regeneration observed during the recovery phase resembles that observed in chronic colitis. 135 Therefore, this recovery model may be useful for studying the wound healing process (epithelial regeneration) and the linkage between innate and acquired immune responses.…”
Section: Tlr2 and Tlr4mentioning
confidence: 99%
“…They showed that these variants correlated with increased expression levels of the nearest gene, PTGER4, which encodes the prostaglandin receptor EP4. Prostaglandin E4 is proinflammatory, triggering the activation of NF-kB, and knockout mouse studies have shown that PTGER4 is involved in the development of colitis [51]. Prostaglandin receptor EP4 is also important in the activation of T reg cells [52 -54] and disruption of this process could contribute to the loss of tolerance to commensal bacteria and to the inflammation that is the hallmark of CD.…”
Section: Likely Functional Roles Of Snps Involved In CD As Identifiedmentioning
confidence: 99%